2003
DOI: 10.1111/j.1745-4514.2003.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Physicochemical Characterization of Starches From Different Banana Varieties

Abstract: The physicochemical properties of the starches extracted from three varieties of banana indigenous to Thailand were investigated. The Thai names of these varieties are Hak Muk, Nam Wa Kom, and Ta Nee. Starch from all three varieties were found to contain 30.9% to 32.0% amylose. Other components were moisture (11.47 to 11.76%), protein (0.22 to 0.93% dry weight basis dwb), lipid (0.07to 0.11 % dwb) and ash (0.07to 0.17% dwb). X‐ray diflraction patterns showed Hak Muk and Nam Wa Kom were of B type whereas Ta Nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
6
2
Order By: Relevance
“…The amylose content showed that plantain starch contained higher amylose than cooking banana starch and amylopectin is high in both starches; hence, they are waxy starches. The amylose content reported for the starches in this study were, however, higher than values reported by Eggleston et al (1992), but lower when compared with the result of Siriwong et al (2003) for banana starch. The pH (3.9-4.6) showed that the starches were acidic.…”
Section: Resultscontrasting
confidence: 89%
See 4 more Smart Citations
“…The amylose content showed that plantain starch contained higher amylose than cooking banana starch and amylopectin is high in both starches; hence, they are waxy starches. The amylose content reported for the starches in this study were, however, higher than values reported by Eggleston et al (1992), but lower when compared with the result of Siriwong et al (2003) for banana starch. The pH (3.9-4.6) showed that the starches were acidic.…”
Section: Resultscontrasting
confidence: 89%
“…The amylose content reported for the starches in this study were, however, higher than values reported by Eggleston et al. (1992), but lower when compared with the result of Siriwong et al. (2003) for banana starch.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations